Difficult differential diagnosis of ectopic germinoma from multiple sclerosis: A case report and literature review. (February 2023) - Masuda, Keisuke; Higa, Nayuta; Yonezawa, Hajime; Uchida, Hiroyuki; Hanaya, Ryosuke
Abstract: Introduction and importance: Intracranial germinomas are germ cell tumors that commonly develop in the pineal or neurohypophysis regions. As ectopic germinomas are rarely observed within the cerebrum and are associated with atypical image findings, diagnosis is challenging. Case presentation: A 14-year-old boy was admitted to our hospital with complaints of vomiting and headache. Gadolinium-enhanced magnetic resonance imaging revealed ring-enhancing lesions in his left frontal lobe and basal ganglia. Susceptibility-weighted imaging indicated that the subependymal veins passing through the lesion centers were engorged, while electrophoretic analysis of cerebrospinal fluid identified oligoclonal bands (OCBs); both were typical of multiple sclerosis (MS). Tumor biopsy revealed many cells with atypical mitotic figures and nuclear enlargements, suggesting malignant disease. As the tumor rapidly proliferated, we opted for surgical excision of the lesions. Histopathological analyses revealed "two-cell patterns" characteristic of germinoma. Immunohistochemistry was positive for placental alkaline phosphatase and c-KIT. The definitive diagnosis was germinoma. After chemoradiotherapy, the patient was discharged without neurological deficits. Clinical discussion: OCBs and several magnetic resonance imaging features (including open ring enhancement, T2 hypointense rims, mild mass effects, mild perilesional edema, peripheral restriction around the lesion, and vessel-like structures running through the lesion center) are useful diagnostic signs for the radiological discrimination of MS from germinoma. However, owing to these factors, some cases are difficult to diagnose. Conclusion: Our case report of an unusual ectopic cerebral germinoma illustrates the difficulty of distinguishing it from MS. Therefore, we recommend proper tissue sampling in such cases, especially in adolescent patients, to make definitive germinoma diagnoses. Highlights: We report a rare case of intracranial germinoma in the frontal lobe and basal ganglia. The engorged subependymal vein in the lesion center is atypical in intracranial germinoma. Proper tissue sampling is required for germinoma diagnoses, especially in adolescents.